Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Define Bernoulli polynomials as: $P_0(x)=1$, $P'_n(x)=nP_{n-1}(x)$, $\int_0^1P_n(x)=0$ if $n\geq1$

Need to prove that for $n\geq2$ we have

$$\sum_{r=1}^{k-1} r^n= \frac{P_{n+1}(k)-P_{n+1}(0)}{n+1}$$

I have already proved that:

$P_n(1)=P_n(0)$ if $n\geq2$ and $P_n(x+1)-P_n(x)=nx^{n-1}$ if $n\geq1$

I tried using induction, but got stuck making the inductive step. Could anybody provide any hints? Thanks!

share|cite|improve this question
up vote 2 down vote accepted

If $$P_n(x+1)-P_n(x)=nx^{n-1}$$ then $$\sum_{x=0}^{k-1} [P_n(x+1)-P_n(x)]=\sum_{x=0}^{k-1} nx^{n-1}$$ but the LHS telescopes to $P_n(k)-P_n(0)$.

share|cite|improve this answer
yes, that is clear enough. thank you! – Sarunas Nov 23 '12 at 22:08

You could use induction on $k$. The equation $P_{n+1}(k+1) = (n+1)k^n + P_{n+1}(k)$ will be useful in the inductive step.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.